PROFILE OF TAX COMPLIANCE RESEARCH IN INDONESIA - Dewi Prastiwi (Media Riset Akuntansi, Auditing & Informasi, 2021)
This study aims to present the profile of tax compliance studies in Indonesia between 2014 and 2019. The method used refers to the systematic review described by Tranfield et al., (2003) from 34 national journals sourced from the Sprott accreditation journal 2.3 and 4. Sprott (Science and Technology Index) is a portal that contains measurements of the performance of Science and Technology which includes the performance of researchers, writers, journal performance, and the performance of science and technology institutions in Indonesia developed by the Ministry of Research, Technology and Higher Education. The results show that: 1) tax compliance research is consistently studied every year; 2) the object of majority tax compliance research is central tax (income tax); 3) tax compliance research in Indonesia raises many issues of economic crime; 4) in an article many test variables that refer to various issues; 5) some articles have not presented theories in explaining the phenomenon or research findings; 6) the discussion in several articles only convey statistical results that have not been accompanied by further analysis. Penelitian ini bertujuan untuk menyajikan profil studi kepatuhan pajak di Indonesia antara tahun 2014 hingga 2019. Metode yang digunakan mengacu pada systematic review yang dijelaskan oleh Tranfield et al., (2003) dari 34 jurnal nasional yang bersumber dari jurnal akreditasi Sprott 2.3 dan 4. Sprott (Indeks Iptek) adalah portal yang memuat pengukuran kinerja Iptek yang meliputi kinerja peneliti, penulis, kinerja jurnal, dan kinerja lembaga Iptek di Indonesia yang dikembangkan oleh Kementerian Riset, Teknologi. dan Pendidikan Tinggi. Hasil penelitian menunjukkan bahwa: 1) penelitian kepatuhan pajak dilakukan secara konsisten setiap tahun; 2) objek penelitian kepatuhan pajak mayoritas adalah pajak pusat (pajak penghasilan); 3) penelitian kepatuhan perpajakan di Indonesia banyak memunculkan isu kejahatan ekonomi; 4) dalam sebuah artikel banyak variabel uji yang mengacu pada berbagai masalah; 5) beberapa artikel belum menyajikan teori dalam menjelaskan fenomena atau temuan penelitian; 6) pembahasan dalam beberapa artikel hanya menyampaikan hasil statistik yang belum disertai analisis lebih lanjut.